2021
DOI: 10.1177/1351010x20984622
|View full text |Cite
|
Sign up to set email alerts
|

Directional sound field decay analysis in performance spaces

Abstract: The analysis of the spatio-temporal features of sound fields is of great interest in the field of room acoustics, as they inevitably contribute to a listeners impression of the room. The perceived spaciousness is linked to lateral sound incidence during the early and late part of the impulse response which largely depends on the geometry of the room. In complex geometries, particularly in rooms with reverberation reservoirs or coupled spaces, the reverberation process might show distinct spatio-temporal charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Previous studies have often reported directional or spatial variations of sound energy decay, decay times or reverberation times [28]- [36], [38]. While this sounds at first like a contradiction compared to our proposed common-slope analysis approach, two explanations for the compatibility of previous study results and our approach are given in the following.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Previous studies have often reported directional or spatial variations of sound energy decay, decay times or reverberation times [28]- [36], [38]. While this sounds at first like a contradiction compared to our proposed common-slope analysis approach, two explanations for the compatibility of previous study results and our approach are given in the following.…”
Section: Discussionmentioning
confidence: 61%
“…Directional sound energy decay variations can be quantified in terms of directional EDFs (DEDFs), as proposed by Berzborn and Vorländer [38]. To this end, we use beamformers with axisymmetric analysis patterns and steer them to different directions, thus obtaining directionally constrained beamformer outputs that can be used to calculate DEDFs.…”
Section: B Room Transition Along a Straight Line: Spatial And Directi...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, rooms lacking good diffusion properties exhibit inhomogeneous and anisotropic decay of sound [4], [15]. Recent work has proposed novel ways to analyze decaying sound fields [16]- [19] while directional decay char-acteristics have also been found to be perceptually important once a certain threshold is met [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that DoA distribution of late reverberation is not isotropic in real measurements using C-C method [6,7] or plane wave decomposition [8,9]. In late reverberation, many sound waves arrive simultaneously or at very close intervals.…”
Section: Introductionmentioning
confidence: 99%